Analisis Pengaruh Disiplin Kerja Guru dalam Melaksanakan Pembelajaran Terhadap Mutu Hasil Belajar Siswa - Yuli Alam (Jurnal Penjaminan Mutu, 2019)
This study aims to analyze the influence of teacher work discipline in implementing learning on quality of student learning outcomes in SMP Negeri 14 Palembang. The respondents in this research are school supervision team, 9th grade teacher (Indonesian, English, Mathematics and Science) and 9th graders of 318 students. Instrument of data collection used is closed questionnaire, interview and student learning outcomes. Data of research result analyzed descriptively and inferensial (using linear regression analysis).The results showed that Indonesian language teacher work discipline influence the students' learning outcomes. As for the subjects of English, Mathematics and Science can be stated there is no influence between the teacher's work discipline on student learning outcomes. One of the factors that determine quality of student learning outcomes is the method of learning. Teaching methods used by teachers should be tailored to the characteristics of learning materials